Albert Camus and the philosophy of the ordinary - Boisvert, Raymond D. (Bloomsbury Academic, 2023)
The standard interpretation keeps repeating that Camus is the prototypical
Keywords: Camus; Albert; Camus; Albert / 1913-1960 / Philosophy; Camus; Albert / 1913-1960 / Criticism and interpretation; Camus; Albert - 1913-1960; Philosophy; Criticism; interpretation; etc; Wertphilosophie; Alltäglichkeit